Agricultural Land Redistribution : Toward Greater Consensus - Binswanger-Mkhize, Hans P.; Bourguignon, Camille; Brink, Rogier van den (World Bank, 2012)
The main focus of this book is land redistribution. To forge greater consensus among practitioners of land reform, and to enable them to make better choices among the many options, the book describes and analyzes alternative broad paths of implementation, using examples and the detailed implementation mechanisms that were used in those examples. The objectives of this book are to review and analyze: a) the growing consensus on the importance of land redistribution; b) the historical origins of land concentration and past attempts to redistribute land; c) ongoing land reform programs, their mechanisms, achievements, and limitations; d) the wide array of objectives, mechanisms, and tools for land redistribution that remain the focus of heated debate; and e) how to develop, implement, and monitor an effective national program of land redistribution.